Meet The Sámi Land Defenders of Scandinavia - Gualinga, Nina (Atmos, 2014)
Four Sami leaders and advocates speak with Nina Gualinga about their relationship to the land, and why the green transition is amounting to a new wave of colonization.

Reclaiming erased lives: archives, records and memories in post-war Bosnia and the Bosnian diaspora - Halilovich, Hariz (Archival Science, 2014)
In this paper, based on conventional and digital ethnography, I first identify three dominant research areas relating to the issues of destruction, use and abuse of archives and records in post-war Bosnia, and discuss their legal, political and ethical dimensions. I then go on to present two ethnographies describing how survivors of ‘ethnic cleansing’ and genocide in Bosnia and in the Bosnian refugee diaspora perceive, experience and deal with missing personal records and material evidence of their histories, as well as how they (re)create their own archives and memories, and in the process reassert their ‘erased’ identities in both real and cyber space. This paper also describes how contemporary technologies—including biomedical technology and information and communication technology—impact the reconstruction of individual and collective identities in shattered Bosnian families and communities in the aftermath of genocide. The ethnographies described point to the novel contribution that these technologies have made to re-humanising both those who perished and the survivors of the war in Bosnia.
Keywords: A&DwP website; Archives; Bosnia; Cyber villages; DNA; Diaspora; Genocide

Antonyms of our remembering - Harris, Verne (Archival Science, 2014)
There are strong dominant discourses across the intersecting spacings of transitional justice, ‘human rights archives’, and reckoning with the past. The power of these discourses can close down non-orthodox perspectives and fresh lines of enquiry. The dual goals of the paper are to identify such lines of enquiry and tease out loose threads in the dominant discourses. The result is a provocation ranging from the experiences of the Nelson Mandela Foundation to the work of deconstruction, from queer theory to legal scholarship, and from personal narrative to documentary film-making. The paper is at once a troubling of dominant discourses and a play with the antonyms of remembering in these discourses.
Keywords: A&DwP website; Community; Deconstruction; Healing; Memory; Spectrality; Transitional justice; Truth commissions

Moving past: probing the agency and affect of recordkeeping in individual and community lives in post-conflict Croatia - J. Gilliland, Anne (Archival Science, 2014)
Reporting on ongoing research, this paper reviews stories, drawn from recent literature as well as gathered through ethnographic research, that people tell about records and recordkeeping during and since the Yugoslav Wars. It focuses on what these stories reveal of the agency and affect of recordkeeping in individual and community lives, particularly in Croatia. The paper concludes with a contemplation of what might be learned from such an approach for the development of recordkeeping infrastructures that can anticipate, avert or alleviate some of the ways in which records and recordkeeping continue to traumatize or target the vulnerable, and frustrate and prevent the human and societal need to “move forward,” if not “move past.”
Keywords: A&DwP website

Break the rules, save the records: human rights archives and the search for justice in East Timor - Robinson, Geoffrey (Archival Science, 2014)
How do distinctive historical experiences and political regimes shape human rights archives? How do those archives and those experiences in turn influence the way painful pasts are remembered or forgotten? And what can historical accounts tell us about the wisdom of prevailing norms and practices regarding the management and control of human rights records? This paper explores these questions through a close analysis of the history and politics of the principal archive documenting human rights abuse in East Timor. It underscores the work of archival studies scholars who argue that human rights archives are always in some degree shaped by the historical and political context in which they emerge and that conflicts over matters of content, mandate, and rules of access are virtually inevitable. Noting that such conflicts typically pit political authorities against victims and their advocates, it argues that successful human rights archival programs hinge critically on sensitive historical and political analysis and that, under certain conditions, human rights archivists should play a more active role in facilitating the pursuit of justice for victims of human rights abuse. It also makes the case for a move away from large, state-controlled archives toward multiple, smaller archives with varied mandates. Finally, it proposes the adoption of a new hierarchy of interest in the management of archives; away from the long-accepted principles of national sovereignty and inalienability, and in the direction of access to the survivors of human rights violations and their advocates.
Keywords: A&DwP website; Archives; East Timor; Human rights; Inalienability; Justice; National interest; Records; Secrecy; Security; Timor Leste; Truth commissions

Stories for Hope–Rwanda: a psychological–archival collaboration to promote healing and cultural continuity through intergenerational dialogue - Wallace, David A.; Pasick, Patricia; Berman, Zoe; Weber, Ella (Archival Science, 2014)
Can archives help heal and extend the benefit of therapeutic interventions in a post-genocide environment? We sought to probe this question through an uncommon collaborative documentation and research project linking psychology and archival science: Stories for Hope–Rwanda (SFH). This intergenerational dialogue project between youth and elder pairs in post-genocide Rwanda draws upon a collective narrative model from psychology and both community and participatory models from archives. The paper reports on three aspects of this endeavor: (1) description of SFH as a process of dialogue generation and archiving; (2) content analysis of the knowledge post-genocide youth sought from their elders; and (3) a qualitative evaluation of what benefits youth and elder pairs reported 6–12 months after their dialogue session, including how participants made use of a personal copy of their dialogue and their decision making and perceptions on making their dialogues more widely available. Specifically, we wanted to know whether psychological benefits would accrue if the silences about genocide could be breached by intergenerational dialogues and whether audio recordings of the dialogues archived for personal, national, and international use could motivate youths and elders over the hurdle of silence and extend the benefits of the dialogues to others. In contrast to interview-driven genocide testimonies, each youth asked an elder to answer some burning questions about the past. In response, elders were directed to share personal, true, and positively helpful stories from their past experiences. Through these efforts, SFH consciously sought to democratize the creation, control, custody, and access to the archive resulting from the recorded dialogues. Based on our analysis, we found that youth were eager to learn most about the genocide (causes, prevention, and stories of loss and survival), followed by family history, marriage, Rwandan culture, living as an orphan, and strategies for forgiveness and reconciliation. We also found that the archival component of the project significantly contributed to both the motivation for participation and the extent of participants’ healing. We conclude that this approach can be productively expanded to other post-conflict and post-genocide communities where silence about a traumatic past reigns triumphant and undermines the ability of youth to map a positive future.
Keywords: A&DwP website; Community archiving; Genocide; Participatory archiving; Psychology; Rwanda; Trauma

Mobilizing records: re-framing archival description to support human rights - Wood, Stacy; Carbone, Kathy; Cifor, Marika; Gilliland, Anne; Punzalan, Ricardo (Archival Science, 2014)
This article seeks to raise consciousness within the field of archival studies in order to foster a generative discussion about how descriptive practices might be expanded, approached differently, or completely rethought. It brings together crosscutting theoretical issues and provides practical examples of mediation in order to mobilize these records in support of human rights work. It first problematizes the foundational archival precept of respect des fonds and its sub-principles of original order and provenance. It then analyzes the necessary transformation of institutional policies and standards in order to foster trust and transparency and identifies structural or system wide strategies for ameliorating past abuses.
Keywords: A&DwP website; Archival description; Archival education; Archival theory; Human rights

The Admissibility of Business Records as Legal Evidence: A Review of the Business Records Exception to the Hearsay Rule in Canada - Force, Donald C. (Archivaria, 2014)
Records professionals play an important role in increasing the likelihood that business records will be admitted as evidence. This article discusses the business records exception to the hearsay rule and the ways in which business records may be tendered as evidence in Canada. By reviewing Canadian case law, the author examines several criteria that could contribute to a judge’s decision to admit a business record as evidence and identifies ways that records professionals can help their organization satisfy each of the criteria. It is argued that the act of sound and structured recordkeeping helps an organization increase the likelihood that its business records will be admitted as evidence. RÉSUMÉ Les spécialistes en gestion de l’information jouent un rôle important afin d’augmenter la probabilité que les documents d’archives des entreprises soient admis comme preuves. Cet article discute du cas des documents d’archives des entreprises comme exception à la règle et il examine les façons dont ils peuvent être mis en adjudication au Canada. En faisant l’étude de la jurisprudence canadienne, l’auteur examine plusieurs critères qui pourraient contribuer à la décision d’un juge d’admettre comme preuve un document d’archives d’entreprise et il identifie les façons dont les spécialistes en gestion de l’information peuvent venir en aide à leur organisation en satisfaisant à chacun de ces critères. L’auteur affirme qu’une gestion des documents solide et structurée permet à une institution d’augmenter la probabilité que ses documents d’archives d’entreprise soient admis comme preuve.
Keywords: A&DwP website

Twenty years of post-apartheid archiving: have we reckoned with the past, or has the past reckoned with us? - Harris, Verne (Journal of the South African Society of Archivists, 2014)
Keywords: A&DwP website

Archives for a Peaceful Future: Case Descriptions - Jones, Briony; Keller, Ingrid Oliveira Silva; Rubli, Sandra (2014)

Brazil Truth Commission Releases Report - The National Security Archive (The National Security Archive, 2014)
Keywords: References - Boel et al. (2021), Archives and Human Rights

The Communist Regime in Romania: Interpretation or Condemnation? - Iacob, Bogdan C. (Sudosteuropa Mitteilungen, 2014)
The article analyses the second life of the concept of genocide In public, scholarly and legal post-2006 discourses about how to deal with the communist past In Romania. It counterpoises such problematic radical condemnations with recent developments In local historical studies. The contribution focuses on a new generation of historians (In their thirties and early forties), exemplifying these approaches by discussing novel studies about repression, Institutions and biographies. It argues that the employment of the term genocide on the one hand reflects specific traditions of public, scholarly and legal narratives about the communist regime. On the other hand, It highlights the ambiguity and misrepresentation of historical phenomena concerning the period from 1945 to 1989 in Romania. Such overbearing denunciatory attitudes potentially obfuscate the complexities and varieties of the past. Benefiting from a genuine archival revolution after 2007, young historians counterbalance opaque, uncritical narratives of victimization with a renewed will for Interpretation and revision. Adapted from the source document.
Keywords: Attitudes; Communists; Genocide; Historians; Narratives; Radicalism; References - Boel et al. (2021), Archives and Human Rights; Repression (Political); Revolutions; Romania

BETWEEN MYTH AND REALITY: THE STASI LEGACY IN GERMAN HISTORY - Jarausch, Konrad (GHI Bulletin Supplement, 2014)
Keywords: References - Boel et al. (2021), Archives and Human Rights

Press Conference by the Chief Cabinet Secretary Wednesday, June 11, 2014 (AM) - Suga, Yoshihide (Prime Minister of Japan and His Cabinet, 2014)
Keywords: References - Boel et al. (2021), Archives and Human Rights

Memory Politics and Ontological Security in Sino-Japanese Relations - Gustafsson, Karl (Asian Studies Review, 2014)
Most international relations (IR) research on the role of collective memory and representations of the past gives the impression that these primarily matter for states constrained internationally by their history as aggressors, such as Japan. How former perpetrator states represent the past is seen as important for bilateral relations because it may affect perceptions in previously victimised states. Representations of the past in the victimised states are seldom dealt with. This article argues that war memory in victimised states is also highly relevant for bilateral relations, since it is closely connected to “ontological security”, or the “security of identity”. By analysing Chinese ofﬁcial documents and Japanese parliamentary debates the article shows how the Chinese government has used representations of the past for ontological security purposes, and how in response Japanese political actors have politicised exhibits at Chinese war museums that are seen as a threat to Japanese identity and interests.
Keywords: References - Boel et al. (2021), Archives and Human Rights

Is China's Discursive Power Increasing? The "Power of the Past" in Sino-Japanese Relations - Gustafsson, Karl (Asian Perspective, 2014)
The idea that China's rise, and more specifically its increased material capabilities, are about to produce a power shift in East Asia raises the question whether the Chinese government's ability to produce effects through discursive power has also increased. The government's use of discourses about China's war against Japan is a conspicuous example of attempts to exercise discursive power. Has China's ability to use the past for political purposes increased as its material capabilities have grown? To answer this question, I theorize on the use of discourses about the past on three levels-domestic, bilateral, and international. My analysis demonstrates that notwithstanding its increased material capabilities, the Chinese government's discursive power has actually decreased.
Keywords: Collective memory; Economic growth; Identity; International relations; Ontology; Political Science; Political Science--International Relations; Political power; Politics; Power; References - Boel et al. (2021), Archives and Human Rights; Studies

Agreement between the United States of America and France, Claims and Dispute Resolution, TREATIES AND OTHER INTERNATIONAL ACTS SERIES 15-1101 - Department of State - United States of America (Department of State - United States of America, 2014)
Keywords: References - Boel et al. (2021), Archives and Human Rights

Archiving justice: conceptualizing the archives of the United Nations International Criminal Tribunal for the former Yugoslavia - Kaye, David (Archival Science, 2014)
The International Criminal Tribunal for the former Yugoslavia (ICTY) will complete its proceedings over the coming years, leaving behind an enormous collection of records. The ICTY archive provides a record of conviction and acquittal, prosecution case and defense response – a vast series of contested facts and arguments. The ICTY winds down with a decidedly mixed reputation, especially among the communities of the Balkans, doing damage to the already-discredited idea of a Tribunal capable of aiding the processes of reconciliation. And yet the UN still speaks of the reconciliatory purposes the ICTY archives may serve. Pursuing reconciliation, however, sets up the archive for failure. It would be better for those establishing the archives to focus on other, attainable goals, taking into account Martha Minow’s caution against judicial records that merely “speak for themselves” (1998). This essay provides historical context for the development of the ICTY archives, outlining its two decades of work, and emphasizes the political context from and into which the archives will emerge.
Keywords: A&DwP website; Balkans; International Criminal Tribunal for the former Yugoslavia (ICTY); International criminal courts; References - Boel et al. (2021), Archives and Human Rights; Truth and reconciliation

The "European Network of Official Authorities in Charge of the Secret Police Files”: A Reader on the Legal Foundations, Structures and Activities (BStU, 2014)
Keywords: References - Boel et al. (2021), Archives and Human Rights

Report of the Special Rapporteur on the promotion of truth, justice, reparation and guarantees of non-recurrence - de Greiff, Pablo (United Nations, 2014)
The Spanish Civil War and the 40 years of dictatorship that followed left a colossal aftermath in terms of victims of serious human rights and humanitarian law violations, including executions, torture, arbitrary detentions, disappearances, forced labour for prisoners and exile.
Keywords: References - Boel et al. (2021), Archives and Human Rights

Resolution adopted by the General Assembly on 18 December 2013 [on the report of the Third Committee (A/68/456/Add.2)] 68/165. Right to the truth - United Nations (United Nations, 2014)
Keywords: References - Boel et al. (2021), Archives and Human Rights

Principles of Access to Archives Technical Guidance on Managing Archives with Restrictions - International Council on Archives (International Council on Archives, 2014)
Keywords: References - Boel et al. (2021), Archives and Human Rights

Transborder access to data and jurisdiction: Options for further action by the T-CY - Ad-hoc Subgroup on Transborder Access and Jurisdiction (Council of Europe, 2014)
Keywords: References - Comma (2020 1-2), Archives and Human Rights

UNITED STATES COURT OF APPEALS FOR THE SECOND CIRCUIT - Docket No. 14‐42‐cv ACLU v. Clapper - United States Court of Appeals (United States Court of Appeals, 2014)
Keywords: References - Comma (2020 1-2), Archives and Human Rights

The role of accessibility in a universal web - Henry, Shawn Lawton; Abou-Zahra, Shadi; Brewer, Judy (W4A '14: International Web for All Conference, 2014)
Universal design" is the process of creating products that are usable by people with the widest possible range of abilities, operating within the widest possible range of situations; whereas "accessibility" primarily refers to design for people with disabilities. While the focus of accessibility is disabilities, research and development in accessibility brings benefits to everyone, particularly users with situational limitations, including device limitations and environmental limitations. Awareness and understanding of the benefits of web accessibility to users without disabilities is growing in some areas with the rapid increase of web-enabled devices such as mobile phones, tablets, televisions, and more; with the increasing focus on the growing number of older web users; and with wider web reach in areas with high incidence of low literacy, low bandwidth, older technology, etc. Although there is significant overlap between designing for accessibility and designing for situational limitations, addressing one set of needs does not necessarily provide sufficient solutions for other needs. Keeping accessibility focused on disabilities encourages research and development on meeting the specific needs of people with disabilities. This communications paper explains the importance of "accessibility" continuing to focus on people with disabilities, while further integrating accessibility with web design, development, and research in other areas, including those covered under universal design and design for all. It also describes how the World Wide Web Consortium (W3C) and Web Accessibility Initiative (WAI) are working to address accessibility and related user needs throughout the technologies of the Web, and invites all interested parties to participate in research and development to further integrate accessibility for people with disabilities in ways that benefit all.
Keywords: References - Comma (2020 1-2), Archives and Human Rights

Defining human rights archives: introduction to the special double issue on archives and human rights - Caswell, Michelle (Archival Science, 2014)
Keywords: References - Comma (2020 1-2), Archives and Human Rights

Identifying Culturally Sensitive American Indian Material in a Non-tribal Institution - Ryan, Ellen M (Society of American Archivists, 2014)
Keywords: References - Comma (2020 1-2), Archives and Human Rights

Who owns the Jewish treasures that were hidden in Saddam Hussein's basement? - PBS News Hour (PBS NewsHour, 2014)
In 2013, Maurice Shohet, an Iraqi Jew who now lives in Washington, D.C., received a surprising email from the National Archives. A librarian had recovered his elementary school record that was left behind nearly 40 years ago when he and his family fled Iraq. The record is part of a cache of thousands of personal documents and religious texts that were found at the start of the Iraq War, drowning in the cellar of a building run by one of the world's most wanted men.
Keywords: References - Comma (2020 1-2), Archives and Human Rights

News from the ICA Human Rights Working Group - 2014-12 (December) - Peterson, Trudy Huskamp (ICA, 2014)

News from the ICA Human Rights Working Group - 2014-11 (November) - Peterson, Trudy Huskamp (ICA, 2014)

News from the ICA Human Rights Working Group - 2014-10 (October) - Peterson, Trudy Huskamp (ICA, 2014)

News from the ICA Human Rights Working Group - 2014-09 (September) - Peterson, Trudy Huskamp (ICA, 2014)

News from the ICA Human Rights Working Group - 2014-08 (August) - Peterson, Trudy Huskamp (ICA, 2014)

News from the ICA Human Rights Working Group - 2014-07 (July) - Peterson, Trudy Huskamp (ICA, 2014)

News from the ICA Human Rights Working Group - 2014-06 (June) - Peterson, Trudy Huskamp (ICA, 2014)

News from the ICA Human Rights Working Group - 2014-05 (May) - Peterson, Trudy Huskamp (ICA, 2014)

News from the ICA Human Rights Working Group - 2014-04 (April) - Peterson, Trudy Huskamp (ICA, 2014)

News from the ICA Human Rights Working Group - 2014-03 (March) - Peterson, Trudy Huskamp (ICA, 2014)

News from the ICA Human Rights Working Group - 2014-02 (February) - Peterson, Trudy Huskamp (ICA, 2014)

News from the ICA Human Rights Working Group - 2014-01 (January) - Peterson, Trudy Huskamp (ICA, 2014)